Penegakan Hukum Terhadap Pelanggaran Hak Cipta Pembajakan Software Komputer Berdasarkan Hukum Positif di Indonesia - Daud Howu-Howu Saro Telaumbanua; I Made Dwi Dimas Mahendrayana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of writing this article is to analyze and understand how the law protects against software copyright infringement so that later we can find out how the law enforcement process works according to positive law in Indonesia. This research uses normative research methods as a reference in analyzing problems based on a statutory approach. The results obtained from this research are that software is a work that is protected by law so that anyone who violates these provisions can be subject to sanctions. Law enforcement proceedings can be filed based on civil proceedings or criminal proceedings and can be carried out in three ways of resolution, namely through alternative settlements, arbitration mediation bodies, or with commercial courts through Intellectual Property Rights.